Influence of the storage on the thermo-oxidative stability of methyl and ethyl esters by PDSC - Bicudo, Tatiana de Campos (2011)
Biodiesel oxidation is a complex process widely influenced by the chemical composition of the biofuel and storage conditions. Several oxidation products can be formed from these processes, depending on type and amount of the unsaturated fatty acid esters. In this work, fatty acid methyl and ethyl esters were obtained by basecatalyzed transesterification of soybean oil and physicochemically characterized according to standards from ASTM, EN, and ABNT. The thermal and oxidative stabilities of biodiesel samples were investigated during the storage process by pressure differential scanning calorimetry (PDSC) and by viscosity measurements. Absolute viscosities of biodiesels after accelerated aging were also determined. The viscosity increased as the aging temperature and time were raised. The results showed that oxidation induction can occur during storage, decreasing the biodiesel stability. PDSC analysis showed that during storage under climate simulation the values of high-pressure oxidative induction times (HPOIT) were reduced for both FAEE and FAME